1997
DOI: 10.1016/s0895-7061(96)00345-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of the angiotensin converting enzyme gene polymorphism with essential hypertension in a chinese population

Abstract: To examine the association between insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene and essential hypertension in a Chinese population, a case-control study was conducted using 157 hypertensive and 115 normotensive subjects. The I/D polymorphism of the ACE gene was identified by polymerase chain reaction. Plasma ACE activity was determined using spectrophotometry. The difference of allele frequencies between normotensives and hypertensives was statistically significant (chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
3
55
0
2
Order By: Relevance
“…Various reports described the D allele as a risk factor for essential hypertension in various populations 6,7 whereas other studies disagree with that hypothesis. [8][9][10][11][12][13] Our work is, to our knowledge, the first one to be done in a Mediterranean population, and reveals no association between the I/D polymorphism and BP (Table 2). When we tested the serum activity of ACE in all of the individuals (fifth quintyl and first quintyl groups) it showed significantly higher values in individuals with more D alleles (DDϾDIϾII).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various reports described the D allele as a risk factor for essential hypertension in various populations 6,7 whereas other studies disagree with that hypothesis. [8][9][10][11][12][13] Our work is, to our knowledge, the first one to be done in a Mediterranean population, and reveals no association between the I/D polymorphism and BP (Table 2). When we tested the serum activity of ACE in all of the individuals (fifth quintyl and first quintyl groups) it showed significantly higher values in individuals with more D alleles (DDϾDIϾII).…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] The D allele was reported to be a risk factor for several cardiovascular diseases including myocardial infarction, left ventricular hypertrophy and essential hypertension in some populations under study, 4-7 but could not later be proven in others. [8][9][10][11][12][13] To our knowledge there is no evidence of any genetic study of ACE performed in a Mediterranean population.…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of the ACE gene I/D polymorphism was performed as described previously. 33,34 Genotyping of the AT 1 R gene A1166C polymorphism was performed with the PCR restriction fragmentlength polymorphism method. 35 For genotyping of AGT gene polymorphisms, we used mini-PCR direct sequencing as described previously.…”
Section: Identification Of Diallelic Polymorphismsmentioning
confidence: 99%
“…Individuals with the I/D polymorphism showed an association with EH in different areas in Japan, 15 but another reports on ACE I/D polymorphism did not appear to have any significant association with variations in BP in Chinese and other Japanese groups. 16,17 Several studies have demonstrated significant age-related associations between ACE I/D polymorphisms and hypertension in gender-specific analyses among different populations, among whom there is association and genetic linkage of the ACE I/D polymorphism with hypertension for males but not for females. 9,18 The DD genotypes were less common in elderly hypertensive Caucasians than in age-matched normotensive subjects.…”
Section: Introductionmentioning
confidence: 99%